Study of physiognomic ear index of new born babies born at maternity ward and birthing center in Tribhuvan university teaching hospital. - Shrestha, Amit (2020)
ABSTRACT: Background The knowledge of physiognomic ear index, physiognomic ear length and breadth is essential for pediatrician to study the association of various defect of ear with clinical conditions or syndromes. Ear abnormality is associated with renal and neurodevelopmental anomalies. Ear parameters are important for forensic experts for identification of an individual. Radiologists can compare the fetal parameter of ear with newborn parameter using MRI and USG.Researcher can use obtained data for future. This research provides data of right and left physiognomic ear length, right and left physiognomic ear breadth as well as right and left physiognomic ear index in male and female Nepalese newborns. Methods A descriptive, observational study was conducted on 165 pairs of ears from Nepalese newborns in Maternity ward and Birthing center of Tribhuvan University Teaching hospital (TUTH).The physiognomic ear length and breadth of newborns were measured. Statistical analysis was done using SPSS 17.0. Results The mean right physiognomic ear index was 68.14±15.26 in male, 68.027±9.82 in female and 68.09±13.13 in both. The left physiognomic ear index was 66.64±8.24 in male, 68.012±13.67 in female and 67.23±10.93 mm in both. The mean right and left physiognomic ear length was 3.5710±0.664 mm in male, 3.3375±0.502 mm in female, 3.4691±0.668 mm in both and 3.574±0.667 mm in male, 3.3389 ± 0.559 in female,3.4708±0.631 mm in both respectively. The mean right physiognomic ear breadth and left physiognomic breadth was 2.3978±0.51478 mm in male,2.2597± 0.42115 mm in bfemale,2.3376±0.479 mm in both and 2.3742±0.528 in male,2.2458±0.442 mm in female and 2.3182±0495 mm in male ,2.2458±0.442 mm in female and 2.3182±0.495 mm in both respectively. Mean Birth weight was 3.0626±0.477 kg and 3.0393±0.448 kg in female, 3.0524±0.463 kg in male female and both. Mean completed days of gestation from LMP was 269±10.522 in male, 271.06±12.358 in female and 270.34± 11.341 in both. Mean hours of life was 16.9852±3.535 in male, 16.4062± 3.58654 in female and 16.73225±3.55865 in both. Mean maternal age was 26.97±4.181 years, 27.15±4.388 in female years and 27.05±4.244 years in both. Positive correlation of birth weight with left physiognomic ear length, left physiognomic ear breadth and right physiognomic ear length(R= 0.176,0.191,0.262) and completed weeks of gestation from LMP with right physiognomic ear breadth, left physiognomic breadth, left physiognomic ear length (R=0.158,0.191,0.165) were observed.. Conclusion This study showed that the right physiognomic ear index ,right physiognomic ear length and breadth is greater in right ear than left ear as suggested by other studies and it also adds dataset of measurement of ears according to the gender ,hours of life ,birth weight and completed weeks of gestation from LMP.